PO.2.38 Anti-β2GPI-domain 1 antibodies stratify high risk of extra-criteria manifestations in a large prospective chinese cohort of antiphospholipid syndrome. (27th September 2022) - Zhou, Y; Qi, W; Zhao, J; Li, M; Zeng, X
Abstract : Purpose: Anti-β2GPI-Domain 1 (β2GPI-D1) antibodies are potentially pathogenic in patients with antiphospholipid syndrome (APS), but their clinical associations were unclear. We aimed to evaluate the clinical characteristics of APS patients with anti-β2GPI-D1 positivity, and its utility in diagnosing APS among SLE patients. Methods: A total of 338 patients were included, of which 169 patients diagnosed with primary APS (PAPS group), 50 with APS secondary to SLE (SAPS group), 209 with SLE (SLE group). Serum anti-β2GPI-D1 IgG was measured using chemiluminescent immunoassay (Inova Company). Extra-criteria manifestations were analyzed, including thrombocytopenia, autoimmune hemolytic anemia, valvular lesions, APS nephropathy, and non-vascular neurological manifestations. Results: Similar presence of anti-β2GPI-D1 IgG was seen among PAPS (32.80%) and SAPS (32.0%) patients, and 96.4% of those with positive anti-β2GPI-D1 IgG showed triple aPLs positivity. Anti-β2GPI-D1 IgG was significantly associated with recurrent thrombosis before APS diagnosis, microscopic thrombosis (p<0.05), but not with adverse pregnancy events ( Figure 1 ). Notably, patients with extra-criteria manifestations, especially thrombocytopenia and APS nephropathy, showed significantly higher titers in anti-β2GPI-D1 IgG (p<0.05). After a median follow-up of twenty-five months, patients with anti-β2GPI-D1 IgG also showed a tendency of more extra-criteria events (3/55 vs 1/114, p=0.095), but not thrombotic events or adverse pregnancy events. Anti-β2GPI-D1 was positive among 8.13% of the SLE controls, and showed higher specificity (91.9%) in diagnosing SAPS among SLE patients as compared to classic aPLs. Conclusions: Anti-β2GPI-D1 IgG had a stronger association with extra-criteria manifestations in APS patients compared to three classic APLs, which properly indicated its pathogenic role of microangiopathy.